Smartphone usage and perceived performance impact : a study on accounting students in Universiti Teknologi Malaysia - Mohamad Ridhwan Ab. Razak 1995- , author 612077 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2018